Answer:
Its the second option.
Step-by-step explanation:
The domain and range are just the x (domain) and y (range) values
Answer:
I think this question is incomplete or maybe incorrect but if it's OK then the answer would be 7x + 5y.
Step-by-step explanation:
the answer remains the same because the question has no like terms so no further calculations can be made.
Answer:
-6
Step-by-step explanation:
2-3x-12=8
-3x=8-2+12
x=18/-3
x=-6
Given:
The equation of a circle is
![x^2+y^2=10](https://tex.z-dn.net/?f=x%5E2%2By%5E2%3D10)
A tangent line l to the circle touches the circle at point P(1,3).
To find:
The equation of the line l.
Solution:
Slope formula: If a line passes through two points, then the slope of the line is
![m=\dfrac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%3D%5Cdfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
Endpoints of the radius are O(0,0) and P(1,3). So, the slope of radius is
![m_1=\dfrac{3-0}{1-0}](https://tex.z-dn.net/?f=m_1%3D%5Cdfrac%7B3-0%7D%7B1-0%7D)
![m_1=\dfrac{3}{1}](https://tex.z-dn.net/?f=m_1%3D%5Cdfrac%7B3%7D%7B1%7D)
![m=3](https://tex.z-dn.net/?f=m%3D3)
We know that the radius of a circle is always perpendicular to the tangent at the point of tangency.
Product of slopes of two perpendicular lines is always -1.
Let the slope of tangent line l is m. Then, the product of slopes of line l and radius is -1.
![m\times m_1=-1](https://tex.z-dn.net/?f=m%5Ctimes%20m_1%3D-1)
![m\times 3=-1](https://tex.z-dn.net/?f=m%5Ctimes%203%3D-1)
![m=-\dfrac{1}{3}](https://tex.z-dn.net/?f=m%3D-%5Cdfrac%7B1%7D%7B3%7D)
The slope of line l is
and it passs through the point P(1,3). So, the equation of line l is
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
![y-3=-\dfrac{1}{3}(x-1)](https://tex.z-dn.net/?f=y-3%3D-%5Cdfrac%7B1%7D%7B3%7D%28x-1%29)
![y-3=-\dfrac{1}{3}(x)+\dfrac{1}{3}](https://tex.z-dn.net/?f=y-3%3D-%5Cdfrac%7B1%7D%7B3%7D%28x%29%2B%5Cdfrac%7B1%7D%7B3%7D)
Adding 3 on both sides, we get
![y=-\dfrac{1}{3}x+\dfrac{1}{3}+3](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B1%7D%7B3%7Dx%2B%5Cdfrac%7B1%7D%7B3%7D%2B3)
![y=-\dfrac{1}{3}x+\dfrac{1+9}{3}](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B1%7D%7B3%7Dx%2B%5Cdfrac%7B1%2B9%7D%7B3%7D)
![y=-\dfrac{1}{3}x+\dfrac{10}{3}](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B1%7D%7B3%7Dx%2B%5Cdfrac%7B10%7D%7B3%7D)
Therefore, the equation of line l is
.